Pollination Requirements and the Foraging Behavior of Potential Pollinators of Cultivated Brazil Nut (Bertholletia excelsa Bonpl.) Trees in Central Amazon Rainforest - M. C. Cavalcante; F. F. Oliveira; M. M. Maués; B. M. Freitas (Psyche: A Journal of Entomology)
This study was carried out with cultivated Brazil nut trees (Bertholletia excelsa Bonpl., Lecythidaceae) in the Central Amazon rainforest, Brazil, aiming to learn about its pollination requirements, to know the floral visitors of Brazil nut flowers, to investigate their foraging behavior and to determine the main floral visitors of this plant species in commercial plantations. Results showed that B. excelsa is predominantly allogamous, but capable of setting fruits by geitonogamy. Nineteen bee species, belonging to two families, visited and collected nectar and/or pollen throughout the day, although the number of bees decreases steeply after 1000 HR. Only 16, out of the 19 bee species observed, succeeded entering the flower and potentially acted as pollinators. However, due to the abundance, flower frequency and foraging behavior of floral visitors, it was concluded that only the species Eulaema mocsaryi and Xylocopa frontalis could be considered relevant potential pollinators.